The Effect Of Cash Turnover, Receivables Turnover, Tax Costs, And Effective Tax Rate On Profitability (Empirical Study Of Manufacturing Companies In The Food And Beverage Sub-Industry Sector Listed On The Indonesia Stock Exchange For The Period 2020-2 - Hylian Tanregudio; Ahmad Junaidi; Furqonti Ranidiah; Nensi Yuniarti (UNIVED Press, 2026)
This study aims to determine the effects of cash turnover, accounts receivable turnover, tax expense, and the effective tax rate on profitability. The study was conducted on food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. Purposive sampling and statistical analysis, including classical assumption tests, were applied using IBM SPSS Statistics version 22. The sample consisted of 23 food and beverage manufacturing companies listed on the IDX. This resulted in 23 companies multiplied by 5 years, producing 115 observations. The results show that cash turnover does not affect profitability, with a significance value of 0.703. Accounts receivable turnover does not affect profitability, with a significance value of 0.889. Tax expense affects profitability, with a significance value of 0.000. The effective tax rate affects profitability, with a significance value of 0.000. Cash turnover, accounts receivable turnover, tax expense, and the effective tax rate simultaneously affect profitability, with a significance value of 0.000 < 0.05 and an Adjusted R Square of 97.6%.